Comparison of fit of poly (etheretherketone) and cobalt-chromium removable partial denture frames: an in-vitro study. - Ary Yaqoub Putros; Jawad Mohammed Mikaeel (Erbil Dental Journal)
Background and objective: the adaptation of the Removable partial denture (RPD) is a key factor in the success of the treatment outcome. This study aims to compare the fit of Poly(etheretherketone)(PEEK) and cobalt-chromium (Co-Cr) frames through the rest seat adaptation